Plastic Waste Management Due to Tourism Activities as an Efforts to Control Marine Pollution on Kuta Beach, Badung Regency - Ni Wayan Yudiani; Nyoman Diah Utari Dewi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Kuta Beach, one of Bali's most iconic coastal destinations, faces severe environmental challenges due to the rapid growth of tourism and inadequate waste management, often leading to a